Coastal metropolis : environmental histories of modern New York City - Zimring, Carl A., 1969-; Corey, Steven H. (History of the urban environment., 2021)
Built on an estuary, New York City is rich in population and economic activity but poor in available land to manage the needs of a modern city. Since consolidation of the five boroughs in 1898, New York has faced innumerable challenges, from complex water and waste management issues, to housing and feeding millions of residents in a concentrated area, to dealing with climate change in the wake of Superstorm Sandy, and everything in between. Any consideration of sustainable urbanism requires understanding how cities have developed the systems that support modern life and the challenges posed by such a concentrated population. As the largest city in the United States, New York City is an excellent site to investigate these concerns. Featuring an array of the most distinguished and innovative urban environmental historians in the field, 'Coastal Metropolis' offers new insight into how the modern city transformed its air, land, and water as it grew. -- Provided by publisher.